The relationship between adiposity and health-related physical fitness among adolescents in Singapore - Chow, Eve Qing Hui (2014)
The main purpose of this study was to determine the relationship between health-related physical fitness variables and adiposity. A cross-sectional study was carried out in a random sample of 148 children 13 to 15 years of age. Anthropometric and HRPF components were measured: estimated body fat percentage (%BF), body mass index (BMI), one-leg sit and reach (SAR), sit-up (SUP), handgrip dynamometer (GT), and the Modified Progressive Aerobic Cardiovascular Endurance Run (PACER). Associations of HRPF with BMI and %BF were examined by partial correlation. Girls has a significantly higher %BF as compared to the boys, although there is no mean difference in BMI found between the two genders. Most health-related fitness test items were positively correlated with each other, with coefficients ranging from 0.258 to 0.873 for boys and 0.291 to 0.934 for girls (P < 0.05). There was only a weak inverse relationship between PACER performance and %BF for boys. Overweight adolescents also possessed relatively higher muscular strength than peers who are of normal or underweight. The various components of HRPF may serve as immediate indicators of potential health risks for underweight and overweight adolescents. Further study on a larger sample size is recommended.